A Dynamic Model of Union Behaviour. The Role of an Endogenous Outside Option and Bargaining Centralisation - Beate Schirwitz; Marcus Dittrich (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2006)
We analyse the role of bargaining centralisation when both the union's outside option and union membership are endogenous and considered in a dynamic framework. A dynamic two-sector model is developed where the wage rate in the first sector is either set by a monopoly union or is the result of efficient bargaining between union and firm. The union's outside option is employment in the second, competitive sector. We extend the dynamic analysis by modelling the outside option as endogenous and show that dynamic models may also overstate employment distortions in this case if bargaining is conducted on a highly centralised stage. Additionally, we offer reflexions along the optimisation process in different scenarios and a comparative static analysis, thus presenting some new general insights into the topic.
Keywords: C61; C78; J51; 330; Dynamic wage bargaining; unions; dual labour market; endogenous outside option; endogenous membership